2012
DOI: 10.1007/s10701-012-9650-z
|View full text |Cite
|
Sign up to set email alerts
|

Modal Quantum Theory

Abstract: The remarkable features of quantum theory are best appreciated by comparing the theory to other possible theories-what Spekkens calls "foil" theories [1]. The most celebrated example of this approach was Bell's analysis [2], which showed that entangled quantum systems have statistical properties unlike any hypothetical local hidden variable model. More recently, there have been several efforts to give quantum theory an operational axiomatic foundation [3,4,5]. In these efforts, a general abstract framework is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
86
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(86 citation statements)
references
References 26 publications
(63 reference statements)
0
86
0
Order By: Relevance
“…Toy theories with this property have been shown to retain fundamental features of quantum theory [34,35]. This solution would imply that quantum theory is only a continuous idealization of a deeper discrete theory.…”
Section: Discussionmentioning
confidence: 99%
“…Toy theories with this property have been shown to retain fundamental features of quantum theory [34,35]. This solution would imply that quantum theory is only a continuous idealization of a deeper discrete theory.…”
Section: Discussionmentioning
confidence: 99%
“…The key variation introduced in [5] is the replacement of the Hilbert space of an N -level quantum system, H C = C N , with a discrete vector space over a finite field: [7,10]. Here, Z q denotes the Galois field GF (q), where q = p n with p prime and n ∈ N. For the n = 1 case, GF (p) is simply Z p = Z/pZ.…”
Section: Galois Field Quantum Mechanicsmentioning
confidence: 99%
“…The six basis transformations in S 3 can be mapped onto the six rotations of the dihedral group D 3 which keep the equilateral triangle abc in figure 1 invariant. ‡ Schumacher and Westmoreland call it an effect in [7] Thus, our 'spins' transform in an analogous way to canonical spin under 'rotations.' However, a significant difference also exists.…”
Section: One-particle Spinmentioning
confidence: 99%
“…In [9], the authors have shown that similarly, one cannot clone an unknown state in Modal Quantum Theory over prime fields. In [14], we obtained the general result that one cannot clone an unknown state in a General Quantum Theory over any division ring.…”
Section: One Cannot Clone An Unknown State In Absolute Quantum Theorymentioning
confidence: 99%
“…In many papers, alternative Quantum Theories have been proposed for classical Quantum Theory (in complex Hilbert spaces, following the København interpretation). For instance, there are a number of papers on "Modal Quantum Theories" (MQTs), which consider similar theories over finite fields (see e. g. [9,7]). Whether the motivation is that these simply serve as toy models for the classical theory, or that they maybe come closer to physical reality, is arguable.…”
mentioning
confidence: 99%